Soft Tissue Sarcoma Cancer Stem Cells: An Overview - Genadry, Katia C.; Pietrobono, Silvia; Rota, Rossella; Linardic, Corinne M. (Frontiers in Oncology, 2018)
Soft tissue sarcomas (STSs) are an uncommon group of solid tumors that can arise throughout the human lifespan. Despite their commonality as non-bony cancers that develop from mesenchymal cell precursors, they are heterogeneous in their genetic profiles, histology, and clinical features. This has made it difficult to identify a single target or therapy specific to STSs. And while there is no one cell of origin ascribed to all STSs, the cancer stem cell (CSC) principle - that a subpopulation of tumor cells possesses stem cell-like properties underlying tumor initiation, therapeutic resistance, disease recurrence, and metastasis – predicts that ultimately it should be possible to identify a feature common to all STSs that could function as a therapeutic Achilles’ heel. Here we review the published evidence for CSCs in each of the most common STSs, then focus on the methods used to study CSCs, the developmental signaling pathways usurped by CSCs, and the epigenetic alterations critical for CSC identity that may be useful for further study of STS biology. We conclude with discussion of some challenges to the field and future directions.